The comparison of the prognostic value of different inflammation-related indicators in patients with oral squamous cell carcinoma - Cheng, Aoming; Wei, Kaixiong; Xu, Qiaoshi; Wang, Chong; Li, Bo; Liu, Huan; Zhang, Lirui; Zhou, Hanchen; Huang, Yu; Zhang, Yiming; Zhang, Xue; Wang, Hao; et al. (Frontiers in Genetics, 2025)
BackgroundThis study aimed to determine the prognostic significance of inflammation markers for patients with oral squamous cell carcinoma (OSCC) and sought to analyze the reasons behind it and its value for clinical guidance.MethodsThis study enrolled 624 patients with OSCC who were surgically treated in our hospital. Clinical baseline data and peripheral blood routine/biochemical parameters were collected within 1 week before surgery. The Kaplan-Meier analysis and Cox multifactor regression analysis were performed for statistical analysis. Time-dependent receiver operating characteristic curves (ROC) were used to explore the timeliness of inflammation-related indicators.ResultsThe Kaplan-Meier analysis revealed that patients with a high-inflammatory trend had significantly shorter overall survival (OS) and disease-free survival (DFS) compared to the patients with a low-inflammatory trend (P < 0.05). Cox multivariate regression analysis demonstrated that advanced lung cancer inflammation index (ALI) and prognostic nutritional index (PNI) were correlated with OS of OSCC patients. Additionally, Subgroup analysis found that ALI and PNI served as independent prognostic factors for OS in male patients. In age-stratified analyses, ALI and PNI also emerged as independent predictors of OS for patients <60 years time-dependent ROC, which ALI demonstrated the best predictive performance for short-term postoperative prognosis (area under the curve (AUC) = 0.74).ConclusionALI and PNI are valuable prognostic indicators in the short term after surgery for young male patients under 60 years old with OSCC.